Una gatta da pelare : vies publiques et vies privées des Italiennes récemment arrivées à Montréal - Vigliano, Chiara (Université de Montréal, 2021)
Keywords: Femmes; Italiens

Romanticism, Home, and Death: Elements in the Lives of the Anglophone Elite in Early Victorian Montreal - Young, Brian (Australian-Canadian Studies, 1997)
Number: 1
Keywords: Anglophones

Les esclaves aux 17e et 18e siècles - Lachance, André (Les marginaux, les exclus et l'autre au Canada aux XVIIe et XVIIIe siècles, 1996)
Keywords: Autochtones; Esclaves; Noirs

Les Irlandais catholiques de Montréal : genèse d'une communauté, 1800-1834 - Duchesne, Jonathan (Université du Québec à Montréal, 2021)
Keywords: Famille; Irlandais; Mariage

Le Montréal juif – (3e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
Number: 3
Keywords: Juifs

Mariage et classes sociales: les Montréalais francophones entre les deux guerres - Girard, Denise (Institut québécois de recherche sur la culture, 2000)
Keywords: Francophones; Mariage

Vivre un choc culturel à 65 ans: le cas des personnes âgées haïtiennes en HLM à Montréal - Bontemps, Eva (Université du Québec à Montréal, 1997)
Keywords: Haïtiens; Logement

Cloisonnement ethnique et solidarité captive. Famille Lao dans le quartier Côte-des-Neiges - Bertheleu, Hélène; Billion, Pierre (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Laotiens; Quartiers

Différenciation sociale et rituels du mariage: les Montréalais francophones, 1925-1940 - Girard, Denise (Université Laval, 1998)
Keywords: Francophones; Mariage

Le phénomène des jeunes de la rue à Montréal le cas des Haïtiens - Uwumuremyi, Marie D'Amour (Université du Québec à Montréal, 1998)
Keywords: Haïtiens; Itinérance

Minorités, majorités et les territoires du quotidien - Ulysse, Pierre Joseph; McAll, Christopher (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

La colocation comme situation de communication interculturelle, le discours de cinq jeunes français vivant avec des québécois - Ferrand, Nathalie (Université du Québec à Montréal, 1999)
Keywords: Français; Locataires; Logement

Structure familiale et pouvoir conjugal dans des familles haïtiennes de Montréal - Lasry, Jean-Claude; Frédérik, Mario (Canadian Ethnic Studies / Études ethniques au Canada, 1986)
Number: 2
Keywords: Famille; Haïtiens

Fréquentations, mariage et divorce chez les Salvadoriens de Montréal - Juteau, Francine (Université de Montréal, 1989)
Keywords: Mariage; Salvadoriens

Dynamiques familiales de la communauté hindoue de Montréal: contrer la violence intrafamiliale - Loiselle, Marguerite (Université de Montréal, 2003)
Keywords: Famille; Indiens

Accéder au meilleur quartier possible: types de famille et ségrégation résidentielle croisée à Montréal - Pelletier, David (Cahiers québécois de démographie, 2012)
issued: 2012-23-00
Keywords: Famille; Quartiers

Marrying ''the Other'': Trends and Determinants of Culturally Mixed Marriages in Québec, 1880-1940 - Gauvreau, Danielle; Thornton, Patricia (Études ethniques canadiennes / Canadian Ethnic Studies, 2015)
Number: 3
Keywords: Britanniques; Irlandais; Juifs; Mariage

''Ils utilisent le passage pour entrer dans notre quartier'' Tensions sociales et interethniques de proximité dans une banlieue montréalaise en transformation - Germain, Annick (Conflits de proximité et dynamiques urbaines, 2013)

Gefilte Fish and Roast Duck with Orange Slices: A Treasure for my Daughter and the Creation of a Jewish Cultural Orthodoxy in Postwar Montreal - Eidinger, Andrea (Edible Histories, Cultural Politics: Toward a Canadian Food History, 2012)
Keywords: Alimentation; Juifs

Regards sur les territoires des ancrages haïtiano-montréalais : les impacts des pratiques transnationales au quotidien - Lanno-Cyr, Sophie (Université de Montréal, 2016)
Keywords: Haïtiens

Logements insalubres en contexte pluriethnique : étude de cas et pistes d'intervention pour le quartier Norgate dans l'arrondissement Saint-Laurent à Montréal - Desmarais, Philippe T. (Université de Montréal, 2016)
Keywords: Arrondissements; Logement; Pauvreté; Quartiers; Saint-Laurent (ville)

City Unique: Montreal days and nights in the 1940s and '50s - Weintraub, William (McClelland & Stewart, 1996)

Le vice et la vertu: le Montréal 1940-1960 - Weintraub, William (Éditions Pierre Tisseyre, 2020)
Translators: _:n57073

«C'est l'eau-de-vie qui a commis ce meurtre». Alcool et criminalité amérindienne à Montréal sous le Régime français - Dickinson, John A. (Études canadiennes / Canadian Studies, 1993)
Number: 35
Keywords: Alcool; Autochtones; Criminalité

Portrait d'un ARGOULET. Pierre Raguideau et la recrue de 1653 à Ville-Marie - Harton, Denis (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2002)
issued: 2002-21-00
Keywords: Autochtones; Engagés; Guerre; Iroquois; Milice

La ville en temps de crise. Montréal et les peintres juifs - Trépanier, Esther (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Guerre; Juifs; Pauvreté; Peinture

L'acculturation alimentaire des immigrants récents de l'Afrique de l'ouest francophone établis à Montréal: une analyse écologique - Pillarella, Sophie (Université du Québec à Montréal, 2006)
Keywords: Africains; Alimentation

Identités et pratiques rituelles au Québec: le mariage comme indicateur des appartenances culturelles - Girard, Denise (Réinventer pays et paysages, 2003)
Keywords: Mariage

Everyday Cosmopolitan Place Making: Multiethnic Commercial Streets in Montreal Neighbourhoods - Radice, Martha (Institut national de la recherche scientifique et Université du Québec à Montréal, 2010)
Keywords: Rues

Les Settlement Houses montréalais et les anglo-protestants. Un écho de la fin du XIXe siècle. Une lumière sur le XXe siècle - Leclair, Micheline (Université du Québec à Montréal, 2000)
Keywords: Anglophones; Protestants

The Living Conditions of Older Latin American Immigrants in Montréal - Puga-Peña, Carmen (Université Concordia, 2006)
Keywords: Latino-Américains

Entre les rues Coloniale et Saint-Urbain. Les Juifs ashkénazes dans les années 1930 - Olazabal, J.-Ignace (Bulletin d'histoire politique, 2001)
issued: 2001-24-00
Keywords: Juifs

Silver and Hotcakes and Beer: Irish Montreal in the 1840s - Olson, Sherry (Canadian Ethnic Studies / Études ethniques au Canada, 2013)
Number: 1-2
Keywords: Auberges; Irlandais

''Tutti a Tavola!'' Feeding the Family in Two Generations of Italian Immigrant Households in Montreal - Cancian, Sonia (Edible Histories, Cultural Politics: Toward a Canadian Food History, 2012)
Keywords: Alimentation; Italiens

Cultural Diversity in Mile End: Everyday Interactions between Hasidim and Non-Hasidim - Alton, Caitlin J. (Université Concordia, 2011)
Keywords: Juifs; Mile End; Quartiers

Vieillir ailleurs: options identitaires et paroles d'aînés d'origine libanaise - El-Hage, Habib (Université du Québec à Montréal, 2010)
Keywords: Libanais

Un jurassien en Amérique du Nord: de Cornol à Montréal, le journal d'Amédée Girard (1893-1897) - Lovis, Marie-Angèle (Presses de l'Université de Montréal, 2017)
Keywords: Suisses

Building the Jewish Community and Claiming “Half the Kingdom”: Women’s Work, Diversity, and Social Justice in Montreal, 1917-2017 - Poutanen, Mary Anne (Juifs d'ici, 2017)
Keywords: Femmes; Juifs; Travail

The Times and Trials of a Distinctive Colony: 1702-1760 - Viau, Roland (Montreal: The History of A North American City, 2018)
Keywords: Alimentation; Artisans; Autochtones; Britanniques; Capitulation; Esclaves; Fortifications; Français; Grande Paix de Montréal; Marchands; Noirs; Seigneurie

Voix des esclaves autochtones et des esclavagistes: un cas d’histoire intersectionnelle dans les archives judiciaires de la juridiction de Montréal - Deslandres, Dominique (Les Cahiers des Dix, 2018)
Number: 72
Keywords: Autochtones; Esclaves

The Montreal Shtetl: Making Home After the Holocaust - Abramson, Zelda; Lynch, John (Between the Lines, 2019)
Keywords: Famille; Juifs; Travail

“Montreal, Open City”. Cultural Conflict and the Making of its Reputation for Corruption, 1890-1960 - Lapointe, Mathieu (Stadt — Macht — Korruption, 2017)
Keywords: Anglophones; Criminalité; Délinquance; Francophones; Prostitution; Réformistes

British Philanthropists and the Imperial Imagination or The Case of the Canadians Distressed by Fire at Montreal - Eamon, Michael (Canadian Historical Review, 2020)
Number: 4
Keywords: Britanniques; Incendies; Philanthropie

Voices of Litigating Women in New France During the Seventeenth and Eighteenth Centuries. - Deslandres, Dominique (Voices in the Legal Archives in the French Colonial World: "The King is Listening", 2021)
Keywords: Autochtones; Esclaves; Femmes; Noirs

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

Sur les traces des immigrants qui se marient dans la vallée du Saint-Laurent pendant la première moitié du XVIIIe siècle - Rompillon-Tran, Samantha (Revue d'histoire de la Nouvelle-France, 2023)
issued: 2023-21-00
Keywords: Français; Mariage

Slavery, Geography and Empire in Nineteenth-Century Marine Landscapes of Montreal and Jamaica - Nelson, Charmaine A. (Routledge, 2016)
Keywords: Africains; Esclaves; Noirs; Paysages; Peinture

Entre rupture et transmission: les pratiques alimentaires italiennes autour du marché Jean-Talon - Masson-Labonté, Amélie; Gagnon, Marie-Anne (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Alimentation; Italiens; Jardins; Marchés

Le Montréal juif – (2e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2021)
issued: 2021-24-00
Keywords: Juifs

Le raz de marée irlandais à Montréal - Olson, Sherry; Thornton, Patricia (Les chemins de la migration en Belgique et au Québec: XVIIe-XXe siècles, 1995)
Keywords: Irlandais

Ethnicity and Housing Adaptation: the Italians in Montreal - Fainella, John G. (Université McGill, 1986)
Keywords: Italiens; Logement

Montreal of Yesterday: A Snapshot of Jewish Life in Montreal During the Era of Mass Immigration - M. Baker, Zachary (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs; Medres; Israel Jonah

Conditions de logement des ménages immigrants et dynamiques métropolitaines à Montréal: une analyse multiniveau exploratoire - Leloup, Xavier (Cahiers québécois de démographie, 2007)
issued: 2007-21-00
Keywords: Logement

Shadrach Minkins: From Fugitive Slave to Citizen - Collison, Gary (Harvard University Press, 1998)
Keywords: Esclaves; Noirs

Se construire et s'affirmer par les lieux. Un regard sur les présences autochtones à Montréal - Comat, Ioana (Université Laval, 2014)
Keywords: Autochtones; Centre d'amitié autochtone

Families, Lovers and their Letters: Italian Postwar Migration to Canada - Cancian, Sonia (University of Manitoba Press, 2010)
Keywords: Famille; Femmes; Italiens

"My Love, How Different Life Is Here..." A Young Italian Woman's Impressions of Postwar Montreal - Cancian, Sonia (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Femmes; Italiens; Langue; Travail

The Governor, the Merchant, the Soldier, the Nun, and their Slaves: Household Formation and Kinship in Seventeenth and Eighteenth-Century Montréal - Loucks, Alanna (Queen's University, 2019)
Keywords: Africains; Autochtones; Dufrost de Lajemmerais; Marie-Marguerite (Youville; Marguerite d'); Esclaves; Famille; Lacorne (famille); Le Moyne de Longueuil; Charles; Noirs

" J’ai vécu des années dans la proximité des Noirs ": Louis Dantin, Stanley et Frances Fields-Johnston – amitié, amour et littérature - Aubé, Mélanie; Hébert, Pierre (Quebec Studies, 2019)
issued: 2019-21-00/2019-22-00
Keywords: Noirs; Poésie; Écrivains

Les " jeunes ", les " amazones ", les " célestes ": les figures de la panique morale sur les drogues à Montréal dans le journal La Patrie, entre 1921 et 1923 - Grenier, Amélie (Bulletin d'histoire politique, 2020)
issued: 2020-22-00
Keywords: Chinois; Criminalité; Femmes; Patrie (La); Réformistes

Dans le Montréal de Papineau. L'aventure de Serafino Giraldi - Aubin, Georges (Montréal en tête, 2011)
issued: 2011-22-00
Keywords: Hôtellerie; Italiens; Papineau (famille); Papineau; Louis-Joseph

Le Montréal juif – (4e partie et fin) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
issued: 2022-22-00
Keywords: Juifs

Divvying up Space: Housing Segregation and National Identity in Early Twentieth-Century Montréal - Sweeny, Robert C. H. (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Locataires; Logement; Quartiers

Actor or Victim? Mario Duliani and His Internment Narrative - Perin, Roberto (Enemies Within: Italians and Other Internees in Canada and Abroad, 2000)
Keywords: Guerre; Italiens

Être des battants quand on est abattus. Implantation et conditions de vie des Québécois d'origine congolaise - Castel, Frédéric (Le Québec APRÈS Bouchard-Taylor: les identités religieuses de l'immigration, 2012)
Keywords: Congolais

Des résistants à Montrealpuram. Implantation et conditions de vie des Québécois d'origine tamoule sri lankaise - Castel, Frédéric (Le Québec APRÈS Bouchard-Taylor: les identités religieuses de l'immigration, 2012)
Keywords: Sri Lankais

Un mémoricide pour mémoire. Implantation et conditions de vie des Québécois d'origine khmère cambodgienne - Castel, Frédéric (Le Québec APRÈS Bouchard-Taylor: les identités religieuses de l'immigration, 2012)
Keywords: Cambodgiens

Un mariage qui aurait tout pour marcher. Implantation et conditions de vie des Québécois d'origine algérienne - Castel, Frédéric (Le Québec APRÈS Bouchard-Taylor: les identités religieuses de l'immigration, 2012)
Keywords: Algériens

Smoke and Fire: The Chinese in Montreal - Kwok Bun, Chan (The Chinese University Press, 1991)
Keywords: Chinois

La famille ouvrière juive à Montréal à la fin du XIXe siècle: le travail et le rôle économique de ses membres - Soucy, Isabelle (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2000)
issued: 2000-23-00
Keywords: Famille; Juifs

Familles montréalaises et élection de tutelle au temps du choléra: genre, appartenance ethnique et pratique judiciaire - Michaud-Guindon, Alexandre (Université du Québec à Montréal, 2019)
Keywords: Choléra; Droit; Famille; Mortalité; Veuvage; Épidémies

Langue et identité dans le Québec du XIXe siècle: une écriture triangulaire - Martineau, France; Avard, Annie (Envoyer et recevoir: lettres et correspondances dans les diasporas francophones, 2006)
Keywords: Famille; Langue

Les Italo-Montréalais [sic] et leur histoire (suite et fin) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2019)
issued: 2019-23-00
Keywords: Guerre; Idéologies; Italiens

Histoire des communautés noires au Québec et à Montréal (1ère partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-21-00
Keywords: Esclaves; Noirs

Trouble at the Edge of Town: Policing Montreal’s Urban Periphery in the Middle of the Nineteenth Century - Horner, Dan (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Irlandais; Lachine (canal); Police

Black Media in Montreal: In Defense of Abyssinia - Williams, Dorothy (Proceedings of the Seventh Annual History in the Making Conference: History and Media, Concordia University, March 2001, 2002)
Keywords: Esclaves; Journalistes; Noirs

Reinforcing racial hierarchy through visual culture : black enslaved children in New France and early Quebec (1700-1834) - Trahan-Thomassin, Marilou (Université McGill, 2019)
Keywords: Enfants; Esclaves; Noirs; Peinture; Publicité

Familles montréalaises du XIXe siècle: trois cultures, trois trajectoires - Olson, Sherry; Thornton, Patricia (Cahiers québécois de démographie, 1992)
issued: 1992-23-00
Keywords: Anglophones; Famille; Irlandais

L’intimité française avec la " sauvagerie " à Montréal aux 17e-18e siècles - Deslandres, Dominique (Dix-huitième siècle, 2020)
issued: 2020/2021
Keywords: Autochtones; Criminalité; Délinquance; Français

Juifs marocains à Paris et à Montréal - Messika, Martin; Cohen, Yolande (Les sépharades du Québec. Parcours d'exils nord-africains, 2017)
Keywords: Juifs; Maghrébins; Mariage; Marocains; Travail

De l'exil à la communauté : une histoire de l'immigration haïtienne à Montréal 1960-1990 - Saint Victor, Alain (Université du Québec à Montréal, 2018)
Keywords: Haïtiens; Travail

Le genre d’une migration post-coloniale: de Meknès (Maroc) à Montréal (Québec) - Cohen, Yolande (Genre et Histoire, 2010)
Number: 6
Keywords: Femmes; Féminisme; Historiens; Juifs; Marocains

Little Burgundy: The Interwoven Histories of Race, Residence, and Work in Twentieth-Century Montreal - High, Steven (Urban History Review / Revue d'histoire urbaine, 2017)
issued: 2017-23-00
Keywords: Chemins de fer; Noirs; Petite-Bourgogne; Quartiers; Travail

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (McGill-Queen's University Press, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."–
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Le Plateau au temps de la guerre (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2015)
issued: 2015-23-00
Keywords: Conscription; Femmes; Fusiliers Mont-Royal; Gares; Guerre; Houde; Camillien; Juifs; Maires; Plateau Mont-Royal; Quartiers; Roman; Tramways; Transport en commun

Les communautés culturelles du Plateau (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2018)
issued: 2018-22-00
Keywords: Allemands; Députés; Godin; Gérald; Grecs; Irlandais; Itinérance; Johns; Emmett (Père Pops); Juifs; Plateau Mont-Royal; Portugais; Poésie; Quartiers; Roumains

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-22-00
Keywords: Chemins de fer; Musique; Noirs; Travail